Ljudje v bližini smrti - Pahor, Majda (Obzornik zdravstvene nege, 2009)
Introduction: Life transitions dying and death are relatively new research issues which in Slovenia have not yet been explicitly elaborated on. Through research the voices of the vulnerable social groups - the dying and their families - will be heard. Methods: Interviews with the dying and their relatives have been conducted within a comprehensive qualitative research study on palliative care in Slovenia. The article presents the analysis of thetranscripts of the interviews through the principles of justified theory. Results: The research enables the collection of voices of the dying and their significant others. The analysis of the statements collected points at the multidimensional processes of dying and bereavement. At the forefront is the experience of bodily change and pain. Psychologically these processed have been described in categories of anxiety, fatigue and lassitude or the positiveexperience of life reflections. Most of the patients do not mention the impending death and some even deny it categorically. The results concerning the social milieu are threefold: the nearest and dearest who simultaneously offer solace and cause concern, the broader social context stigmatizing their condition and finally the hospital environment which offershelp and support but also generates suffering. The analysis of the interviews identified two main categories, namely, the experience of medical help and the experience of self. Discussion: The dying and their families arevulnerable groups for whom new integrated forms of care should be developed on all levels of healthcare.
Keywords: Paliativna oskrba; Palliative care; svojci; Teminalna oskrba; Terminal care; umirajoči